Review; Pharmacovigilance and Drug Safety: A Global Perspective - Shivamurthi, T.; Dixit , D. Chaitanya; Ramachandra, M. Sri (Asian Journal of Pharmaceutical Research and Development, 2025)
A significant and essential component of clinical research is pharmacovigilance. Throughout the product lifecycle, post-marketing pharmacovigilance and clinical trial safety are both crucial. The pharmacological science that deals with the identification, evaluation, comprehension, and avoidance of negative consequences is known as pharmacovigilance. What is known about its advantages and disadvantages, difficulties, and prospects in Indian medicine? Here, the primary emphasis is on the objectives and function of pharmacovigilance in the regulation of medications and their partners. including the short- and long-term negative consequences of medications. In India, pharmacovigilance is still in its infancy, and very little is known about the field. Although the field of pharmacovigilance has made significant strides in western nations, nothing has been accomplished inIndia chose to join the Uppasla Centre for Adverse Event Monitoring at that time. With the help of the media and regulatory bodies, pharmacovigilance has become increasingly important as people have grown more knowledgeable about the risks and benefits of medications. Any unfavourable medical event that may arise when taking a medication but is not always connected to its use is referred to as an adverse event. "An adverse drug reaction is any unpleasant, unexpected, and undesirable side effect of a medication that happens at dosage used in humans for diagnosis, treatment, prevention, or alteration of physiological function." In order to collect safety data for early detection, spontaneous reporting of adverse drug reactions and events is a crucial tool. A growing number of Indian businesses have emerged in recent years. In 2008, this is really recent data and has been used here since most recent and relevant data available are of this year. Available, it was estimated that (ADRS) accounted for 5% of the total amount of reports, thus minimizing the number of times that honest adverse reaction reports were being eliminated